The Extent of Collective Bargaining in Canada - Adams, Roy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
The author attempts to improve upon a certain number of collective bargaining coverage estimates mainly by reviewing union membership data in Canada.